Purification, characterization and cytotoxicity assessment of Ageritin: The first ribotoxin from the basidiomycete mushroom Agrocybe aegerita - Landi, Nicola; Pacifico, Severina; Ragucci, Sara; Iglesias, Rosario; Piccolella, Simona; Amici, Adolfo; Di Giuseppe, Antonella M.A.; Di Maro, Antimo (Biochimica et biophysica acta. General subjects, 2017)
Several species belonging to Ascomycota phylum produce extracellular ribonucleases, known as ribotoxins, which exhibit RNase activity through the cleavage of a single phosphodiester bond, located at the universally conserved sarcin/ricin loop of the large rRNA leading to inhibition of protein biosynthesis. Clarifying the structure-function relationship in ribotoxins is interesting for their use in human tumour therapy and in construction of pest resistant transgenic plants. The ribotoxin Ageritin has been isolated for the first time from the Basidiomycetes class. The enzyme, characterized by means of its amino acid composition, N-terminal sequence and a circular dichroism, structurally differs from Ascomycota ribotoxin prototype, although it was able, as α-sarcin, to release a specific α-fragment. However, it does not display aspecific ribonucleolytic activity. Ageritin exerts cytotoxicity and cell death promoting effects towards CNS model cell lines (SK-N-BE(2)-C, U-251 and C6), as vinblastine, a plant alkaloid used in cancer therapy. Moreover, our results indicate that Ageritin initially activates caspase-8, whereas caspase-9 cleavage was not detected, demonstrating the involvement of an extrinsic apoptotic pathway. Our findings show that Ageritin is the earliest diverging member of the Ascomycota ribotoxin family, suggesting that ribotoxins are more widely distributed among fungi than previously believed. Ageritin, structurally different from the widely known Ascomycota ribotoxins, with promising anti-cancer properties vs. aggressive brain tumours, has been found from the basidiomycete fungus Agrocybe aegerita. Finally, this finding highlights that the ribotoxin family has divergent members in Basidiomycota phylum, whose structural and functional characterization can give new information on ribotoxin or ribonuclease superfamilies. [Display omitted] •Ageritin is a ribotoxin purified from Agrocybe aegerita mushroom.•This enzyme is the first ribotoxin from the Basidiomycetes class.•Ageritin is enzymatically similar to alpha-sarcin, a ribotoxin prototype.•This protein is structurally different from the widely known Ascomycota ribotoxins.•Ageritin inhibits the cell proliferation of several CNS model cell lines via apoptosis.